Lingua Cultural Aspects of Language (Eurasian Journal of Philology Science and Education, 2016)
The article deals with lingua cultural aspects of language. Nowadays these aspects of language in comparison with other fields of linguistic study are comparatively new. We know that lingua cultural aspect of linguistic science appeared at the beginning of the XX century. Investigations show that it gradually ejected country study. Despite the fact that linguacultural science (as we call it culturology) is a new field of investigation, methodological foundations of study of problems of language and culture interactions are being formed. We have tried to show some of them in this research work. This research covers the description of the criteria of complex consideration of the problem. It includes the necessity of determination of the borders of lingua culturology and teaching this subject at schools and universities because lingua cultural information becomes a necessary communicative part of the competence of every student, specific manner, which are realized in the semantics of language unit. As we know, linguacultural science studies interrelation of language and culture, but it is different from cultureoriented linguistics and we paid attention to the linguistic aspect in this article. In this research work we have tried to determine the object of investigation of culturology and discover types of culture, its layers, its connections with other fields of sciences. More attention in the study of cultural science is paid to cultural, social state and national features of people speaking this or that language and possessing the culture with all its selfbelonging peculiarities.
Keywords: сulturology; investigation; linguistic aspect; competence; communicative approach; interrelation of language